Estimation of absorbed doses in patients’ organs from the released radionuclide-label during radionuclide therapy with 225Ac - A. E. Petrova; L. A. Chipiga; A. V. Vodovatov; A. A. Stanzhevsky; D. N. Maystrenko; A. A. Lumpov; A. B. Sinyukhin; I. V. Boykov; T. E. Rameshvili (Радиационная гигиена, 2022)
Today, the treatment of cancer with the use of radiopharmaceuticals is a developing method all over the world. The preparation of the radiopharmaceuticals and its quality control prior to its administration to the patient is one of the important elements of nuclear medicine procedures. The instability of the compound can lead to a change in the distribution of the radionuclide in the patient’s body, a decrease in the effectiveness of treatment, as well as to unjustified irradiation of healthy organs and tissues. The aim of this work was to estimate the absorbed doses in human organs and tissues during radionuclide therapy using 225Ac for the case of the 225Ac release. The absorbed doses were calculated for the model presented in ICRP Publication 141 for healthy people. This model consists of 18 cameras (blood, cortical volume, cortical surface, cortical red bone marrow, trabecular volume, trabecular surface, trabecular red bone marrow, kidneys (two chambers), bladder, liver (two chambers), gonads, contents of the small intestine, contents of the upper large intestine, soft tissues. Time-integrated activities were calculated using the specialized software SAAM II v2.3. The calculation of absorbed doses was performed using the IDAC-Dose 2.1 software. The highest absorbed doses were obtained for liver, testes, ovaries and red bone marrow, which leads to an increase in doses in these organs in comparison with doses from 225Ac-PSMA up to a factor of two. A change in the biodistribution of 225Ac in a patient’s body, associated with the release of a radionuclide from the radiopharmaceuticals, can lead to an increase in doses in healthy radiosensitive organs and tissues, as well as to a decrease in the effectiveness of treatment.